Stochastic stability in monotone economies - John Stachurski; Takashi Kamihigashi (Theoretical Economics, 2014)
This paper extends a family of well-known stability theorems for monotone economies to a significantly larger class of models. We provide a set of general conditions for existence, uniqueness and stability of stationary distributions when monotonicity holds. The conditions in our main result are both necessary and sufficient for global stability of monotone economies that satisfy a weak mixing condition introduced in the paper. Through our analysis we develop new insights into the nature and causes of stability and instability.
Keywords: C62; C63; 330; Stability; monotonicity; stationary equilibria